The role of organizational culture on employee engagement - Bilalli Abduraimi, Pakize; Mustafi, Mahije; Islami, Xhavit (Business: Theory and Practice, 2023)
Despite the recognized importance of organizational culture (OC) for favorable organizational effects, empirically is relatively little known about its impact on employee engagement (EE), in Balkan countries, especially in the Republic of North Macedonia. To address this gap the purpose of this study is to explore the relationship between OC components and three dimensions of EE (vigor, dedication and absorption). To conduct this study a survey of 152 public secondary education employees who operate in the Republic of North Macedonia was done. The gathered data was analyzed using SPSS program. Results indicated that several components of the OC are significantly related to EE dimensions, such as employee vigor, dedication, and absorption. As a result, the study concludes that OC has a significant positive effect on EE dimensions both in and out of school. The outcomes of this study significantly contribute to a better understanding of the OC-EE relationship in the non-profit organizations.